Variable-Volume Kinetic Model to Estimate Absolute Blood Volume in Patients on Dialysis Using Dialysate Dilution. Issue 1 (January 2018) - Samandari, Hamed; Schneditz, Daniel; Germain, Michael J.; Horowitz, Joseph; Hollot, Christopher V.; Chait, Yossi
Abstract : Long- and short-term adverse outcomes in hemodialysis (HD) have been associated with intradialytic hypotension, a common HD complication and significant cause of morbidity. It has been suggested that knowledge of absolute blood volume (ABV) could be used to significantly improve treatment outcomes. Different dilution-based protocols have been proposed for estimating ABV, all relying on the classic mono-exponential back-extrapolation algorithm (BEXP). In this paper, we introduce a dialysate dilution protocol and an estimation algorithm based on a variable-volume, two-compartment, intravascular blood water content kinetic model (VVKM). We compare ABV estimates derived using the two algorithms in a dialysate dilution study including three arterio-venous (AV) and three central-venous (CV) access patients, and multiple bolus injection tests (3–5) within each of several (2–6) HD treatments. The distribution of differences between ABV estimated from the two methods showed negligible systematic difference between the mean values of ABVs estimated from the BEXP and VVKM algorithms, however, the VVKM estimates were 53% and 42% more precise for the CV and AV patients, respectively. Good agreement was observed between measured and VVKM-estimated blood water concentration with the root-mean-square error (RMSE) less than 0.02 kg/kg (2%) and 0.03 kg/kg (3%) for AV and CV patients, respectively. The dilution protocol and the new VVKM-based estimation algorithm offer a noninvasive, inexpensive, safe, and practical approach for ABV estimation in routine HD settings.